Ways to improve administrative and legal mechanism for ensuring the rights of business entities in the field of taxation - A. M. Chorna (Law and Safety)
The author of the article, based on the analysis of scientific views of scholars and current legislation of Ukraine, elaborates the ways to improve administrative and legal mechanism for ensuring the rights of business entities in the field of taxation. It is substantiated that the objective prerequisites for improving administrative and legal mechanism for ensuring the rights of business entities in the field of taxation are: 1) low level of trust of entrepreneurs in the tax service; 2) high level of corruption in the agencies of the State Tax Service; 3) imperfect mechanism of legal regulation of tax advice; 4) low level of quality and efficiency of functioning of administrative and legal mechanism of ensuring the rights and lawful interests of business entities as taxpayers, etc. It was stated that the first step towards improving administrative and legal mechanism for ensuring the rights of business entities in the field of taxation should be the improvement of the relevant administrative legislation. The expediency of improving the organizational structure of the State Tax Service is substantiated. Emphasis was placed on the need to improve the interaction of the State Tax Service with other public authorities and the public on ensuring the rights of business entities in the field of taxation. It is noted that the deep and constructive interaction of the State Tax Service of Ukraine with other public authorities and the public is undoubtedly an important guarantee of high quality and efficiency for ensuring the rights of business entities.